PENENTUAN LAJU PENURUNAN KADAR AIR OPAK SINGKONG DENGAN MENGGUNAKAN RUANG PENGERING BERENERGI BIOMASSA LIMBAH PELEPAH KELAPA SAWIT - Malik, Usman; Sihotang, Weldo (Komunikasi Fisika Indonesia, 2016)
The research was conducted to determine the declining rate water content of cassava using biomass energy from palm fronds. Drying is done by using a drying chamber with a length of 130 cm, width 90 cm and high 120 cm. The drying chamber is formed in such a manner that is equipped with a chimney, two-level drying rack and 2 drums as heat sources. Drying heat sources derived burning biomass from palm fronds in the drum. The room walls are made of plywood with thickness of 8 mm and coated zinc plate with a thickness of 1 mm which is painted black. Samples were dried cassava is opaque and produced in Rejosari Village, District Tenayan Raya, Pekanbaru. First mass each opaque cassava in the rack 1 at 44.13 grams, 41.99 grams, and 46.27, while in the rack 2 of 47.66 grams, 45.02 grams and 45.98 grams. Drying is carried out for 100 minutes with 10 minute intervals where the room temperature is set about 50 Â° C to 65 Â° C. The decline in the water content on average on both a rack every 10 minutes for observation 100 minutes are 15.30%, 10.62%, 8.84%, 7.17%, 6.40%, 5.78%, 4.71%, 3.74%, 2.75%, 2.52%.